Editorial, Volume 7, Issue 2 - Kristy L Archuleta (Journal of Financial Therapy, 2016)
This issue features four articles, two profiles, and one book review. Each article adds a new contribution to the field of financial therapy. First, Dr. Asebedo applies a conflict resolution framework to money arguments. Next, Drs. Rea, Zuiker, and Mendenhall explore financial management practices among emerging adult couples. In the third paper, Drs. Ann Woodyard and Cliff Robb help to add further description of financial satisfaction. Then, Dr. Russell James offers a unique theoretical analysis of mortality salience and financial decisions. This issue also features a practitioner profile of Beth Crittenden and a scholar profile of Sarah Asebedo. Finally, we conclude with a review by Neal VanZutphen about a book entitled, The Seven Principles for Making Marriage Work.
Keywords: financial therapy; financial well-being; financial planning; financial counseling; mental health; therapy